Fe-based amorphous alloy and its manufacturing method

JP7637341B2Active Publication Date: 2025-02-28DAIDO STEEL CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020029290
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-02-25
Publication Date
2025-02-28
Estimated Expiration
2040-02-25

AI Technical Summary

Benefits of technology

【0017】 上記した発明において、98%以上のアモルファス化率を与えるように急冷凝固することを特徴としてもよい。かかる特徴によれば、結晶相を実質的に含むことなく、高い飽和磁束密度と低い保磁力とを具備するFe基アモルファス合金を高い製造性を持って得られるのである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637341000001
    Figure 0007637341000001
  • Figure 0007637341000002
    Figure 0007637341000002
  • Figure 0007637341000003
    Figure 0007637341000003
Patent Text Reader

Abstract

To provide an Fe base amorphous alloy that has, even though it is an amorphous phase alone, a high saturation magnetic flux density and a low coercive magnetic force, and is excellent in producibility, and to provide a method for producing the same.SOLUTION: Provided is an Fe base amorphous alloy, which is an amorphous single-phase alloy that contains as, in atom %, Si: 1 to 5%, B: 5.5 to 13%, C: 1 to 7%, P: 0.1 to 4% to Fe, where Si+B+C<15.0%, together with unavoidable impurities, and in which, characterized, Fe is 82 to 85%, the saturation magnetic flux density Bs is larger than 1.60 [T], and the coercive force Hc is less than 10 [A / m]. Said alloy is produced by controlling quick chilling solidification.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an Fe-based amorphous alloy having a high saturation magnetic flux density and a low coercive force, and a method for producing the same. [Background technology]

[0002] In recent years, soft magnetic alloys used in electronic components such as in-vehicle reactors are required to have high saturation magnetic flux density and low coercive force due to the trend of shifting the frequency band used to higher frequencies. It is known that the crystal grain size of a ferromagnetic material can be reduced to a predetermined value or less to average the crystal magnetic anisotropy and reduce the coercive force. Therefore, a method has been proposed in which an amorphous soft magnetic alloy is heat-treated to disperse fine crystal grains in the amorphous phase to obtain a low coercive force and to obtain a soft magnetic alloy with soft magnetic properties such as high magnetic permeability and low iron loss.

[0003] For example, Patent Document 1 discloses an Fe-Si based soft magnetic alloy in which fine α-Fe crystal grains are crystallized in an amorphous base. 100-a-b-c-d S a B b C c Cu d (where a, b, c, d are expressed as atomic %, 1%≦a≦3%, 9%≦b≦14%, 1%≦c≦4%, 0.3%≦d≦1.5% and 80%≦100-abcd≦86%), and the amorphous alloy obtained by rapid solidification is heat treated to crystallize α-Fe crystal particles with nano-sized particle size. Here, Cu is added to the Fe-Si alloy along with semi-metallic elements such as B and C, but it is stated that if the Fe concentration exceeds 86 at%, it is not possible to obtain a homogeneous rapidly quenched amorphous ribbon by the single roll method.

[0004] Patent Document 2 discloses an Fe-based soft magnetic alloy in which fine α-Fe crystal grains are crystallized in an amorphous base by heat treatment. The alloy is generally said to have an alloy composition in which Ni, Co, and rare earth metals, which are said to give a paramagnetic alloy, are added to Fe, and various other additive elements are added, but it is stated that the Fe content in the entire soft magnetic alloy should be 70 atomic % or more. It also states that such a two-phase alloy has a higher saturation magnetic flux density and a lower coercive force than an alloy consisting of a single amorphous phase. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-94651 A [Patent Document 2] JP 2016-148004 A Summary of the Invention [Problem to be solved by the invention]

[0006] As mentioned above, it is said that in Fe-based soft magnetic alloys, high saturation magnetic flux density and low coercivity can be obtained by dispersing fine α-Fe crystal particles in an amorphous base material through heat treatment. However, a heat treatment process is required to disperse fine α-Fe crystal particles, and it is difficult to control the heat treatment conditions to obtain an optimal dispersion state, which places restrictions on the manufacturing process.

[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an Fe-based amorphous alloy which is an amorphous phase alone but has high saturation magnetic flux density and low coercive force and is excellent in manufacturability, and a method for producing the same. [Means for solving the problem]

[0008] The Fe-based amorphous alloy of the present invention is an amorphous single-phase alloy containing, in atomic %, Fe together with unavoidable impurities in the form of 1-5% Si, 5.5-13% B, 1-7% C, and 0.1-4% P, where Si+B+C<15.0%, and is characterized in that the alloy contains 82-85% Fe, has a saturation magnetic flux density Bs greater than 1.60 [T], and has a coercive force Hc less than 10 [A / m].

[0009] According to these characteristics, the alloy is substantially amorphous and single-phase without suppressing the amount of Fe, while having high saturation magnetic flux density and low coercive force, and is also easy to manufacture.

[0010] The above-mentioned invention may be characterized in that the contents are 1-2% Si, 10-13% B, and 1-2% C. According to this characteristic, an Fe-based amorphous alloy that is substantially an amorphous single phase but has a higher saturation magnetic flux density and a lower coercive force can be obtained with high manufacturability.

[0011] In the above-mentioned invention, the composition may be characterized in that it contains Cu in an amount of 0.3% or less by atomic percent. According to this characteristic, the inclusion of Cu is permitted without affecting the amorphous forming ability, the saturation magnetic flux density, or the coercive force.

[0012] The above-mentioned invention may be characterized in that it has an amorphous ratio of 98% or more. With this characteristic, it is possible to maintain a high saturation magnetic flux density and a low coercive force without substantially containing a crystalline phase, and it is not necessary to control the crystalline phase, and it is also easy to manufacture.

[0013] The method for producing an Fe-based amorphous alloy of the present invention is characterized in that a master alloy containing, in atomic %, Fe together with unavoidable impurities of 1-5% Si, 5.5-13% B, 1-7% C, and 0.1-4% P, where Si+B+C<15.0%, is melted, and the master alloy is rapidly solidified to have an amorphous single phase, 82-85% Fe, a saturation magnetic flux density Bs greater than 1.60 [T], and a coercive force Hc less than 10 [A / m].

[0014] According to this feature, it is possible to obtain an Fe-based amorphous alloy with high manufacturability, which is substantially amorphous single phase without suppressing the Fe content and has high saturation magnetic flux density and low coercive force.

[0015] In the above-mentioned characteristics, the composition may be characterized in that the Si content is 1-2%, the B content is 10-13%, and the C content is 1-2%. According to such characteristics, the Fe-based amorphous alloy can be substantially made to have an amorphous single phase without suppressing the Fe content, and thus the Fe-based amorphous alloy having a higher saturation magnetic flux density and a lower coercive force can be obtained with high manufacturability.

[0016] In the above-mentioned invention, the master alloy may contain, in atomic percent, 0.3% or less of Cu. According to this feature, the inclusion of Cu is permitted without affecting the amorphous forming ability, saturation magnetic flux density, or coercive force.

[0017] In the above-mentioned invention, the alloy may be rapidly solidified to give an amorphous ratio of 98% or more. According to this feature, an Fe-based amorphous alloy having a high saturation magnetic flux density and a low coercive force without substantially containing a crystalline phase can be obtained with high manufacturability. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 is a flow diagram showing a method for producing an Fe-based amorphous alloy according to the present invention. [Diagram 2] 1 is a table showing the composition of the alloys used in the manufacturing tests and the properties of the obtained alloy ribbons. [Diagram 3] 1 is a table showing the composition of the alloys used in the additional manufacturing test and the properties of the obtained alloy ribbons. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] A method for producing an Fe-based amorphous alloy as one embodiment of the present invention will be described with reference to FIG.

[0020] As shown in Fig. 1, first, an Fe-Si based soft magnetic alloy is melted (S1) as a mother alloy of an Fe-based amorphous alloy. Here, as the mother alloy, an alloy having a composition containing, in atomic %, Fe: 1-5% Si, 5.5-13% B, 1-7% C, and 0.1-4% P, with the proviso that Si+B+C<15.0%, is used.

[0021] In an alloy with such a composition, the saturation magnetic flux density of the Fe-based amorphous alloy obtained can be increased by containing a relatively large amount of Fe. However, if the Fe content is too large, the amorphous formability is reduced. Therefore, in addition to the above, the Fe content in the obtained amorphous single phase alloy is set to be within the range of 82 to 85 atomic %. In addition, the Si-BC composition was examined to increase the amorphous formability, and Si+B+C<15.0% was set as described above. As a result, it became possible to contain a relatively large amount of Fe while suppressing the decrease in the amorphous formability, and to obtain a high saturation magnetic flux density.

[0022] The mother alloy can also contain Cu at 0.3 atomic % or less. The inclusion of a small amount of Cu, which is a non-magnetic material, does not affect the magnetic properties of the resulting Fe-based amorphous alloy.

[0023] Next, the molten mother alloy is rapidly solidified (S2). For example, a single roll method can be used for the rapid solidification. In the single roll method, the molten mother alloy is extracted onto the surface of a copper chill roll rotating at high speed, and is rapidly solidified on the surface of the chill roll. This rapid solidification can provide an alloy ribbon consisting of a thin amorphous single phase body. Here, the peripheral speed of the chill roll is preferably within a range of 20 to 30 m / s to rapidly cool the molten alloy, thereby making the alloy ribbon an amorphous single phase. Here, the amorphous single phase refers to an amorphous ratio of 98% or more.

[0024] The alloy ribbon obtained in this way has no crystalline magnetic anisotropy and low coercive force because it is amorphous single phase. By making it an amorphous single phase that does not substantially contain a crystalline phase, control of the crystalline phase is not required, and as a result, it is easy to manufacture. In addition, by making the Fe content relatively high at 82 atomic % or more, it is possible to obtain a high saturation magnetic flux density. Specifically, as soft magnetic properties, the coercive force Hc can be made smaller than 10 [A / m], and the saturation magnetic flux density Bs can be made larger than 1.60 [T].

[0025] In addition, among the component compositions of the above-mentioned master alloy, it is also preferable that the contents of Si, B and C are Si: 1-2%, B: 10-13%, and C: 1-2%. With such a component composition, it is possible to obtain an Fe-based amorphous alloy having a higher saturation magnetic flux density and a lower coercive force.

[0026] [Manufacturing test] Next, the results of actually producing and testing an Fe-based amorphous alloy will be described with reference to Figs. 2 and 3.

[0027] (1) Manufacturing of Fe-based amorphous alloys First, the alloys with the respective component compositions shown in Figure 2 were melted and rapidly solidified using a single roll method to produce alloy ribbons as Fe-based amorphous alloys.

[0028] (2) Measurement of soft magnetic properties The soft magnetic properties of the manufactured alloy ribbons were measured in terms of saturation magnetic flux density Bs and coercive force Hc. The saturation magnetic flux density Bs was measured using a vibrating sample magnetometer, and the coercive force Hc was measured using an Hc meter (coercive force meter).

[0029] (3) Measurement of crystallization rate The crystallization rate of the manufactured alloy ribbon was further investigated. The crystallization rate was calculated from the XRD pattern. In detail, the total integrated intensity I T Area intensity of crystalline peak (half width < 5°) for I CIn other words, the crystallization rate (%) = I C / I T × 100. Here, the amorphous ratio is (100-crystallinity)%, and the crystallinity, which is a measured value, was used for evaluation.

[0030] (4) Evaluation The manufactured alloy ribbons were evaluated for soft magnetic properties and crystallization rate. As for soft magnetic properties, saturation magnetic flux density Bs greater than 1.60 [T] was evaluated as good. Coercive force Hc less than 10 [A / m] was evaluated as good. In addition, crystallization rate of 2% or less was evaluated as good, since it was essentially made of a single amorphous phase.

[0031] (5) Test results As shown in FIG. 2, Examples 1 to 9 were evaluated as being good in all of the saturation magnetic flux density Bs, coercive force Hc, and crystallization rate.

[0032] On the other hand, in Comparative Example 1, the crystallization rate reached 3.0% and the coercive force Hc was as large as 15.5 [A / m]. This was thought to be because the Fe content was relatively high at 85.5 atomic %, which promoted crystallization during rapid solidification of the molten alloy.

[0033] In Comparative Example 2, the crystallization rate was as high as 65%, and the coercive force Hc exceeded 2500 [A / m]. Although Si is an element responsible for amorphous formation, it was thought that the excessive content of 10.8 atomic % reduced the amorphous forming ability instead.

[0034] In Comparative Example 3, the crystallization rate was large at 3.1%, and the coercive force Hc was large at 15.0 [A / m]. Although C is an element responsible for amorphous formation, it was contained in a large amount at 10.8 atomic %, which is thought to be because it lowered the crystallization temperature from the amorphous phase, induced the crystallization of crystal grains, and ultimately reduced the amorphous forming ability.

[0035] In Comparative Example 4, the crystallization rate was as high as 31.1%, and the coercive force Hc exceeded 2500 [A / m]. This was thought to be because the C content was low, which reduced the amorphous forming ability.

[0036] In the comparative example 5, the saturation magnetic flux density Bs was a small value of 1.55 [T]. The total content of Si, B and C (Si+B+C) exceeded 15.0 atomic % to 15.3 atomic %, and as a result, the content of Fe was reduced to 80.7 atomic %, which was considered to have caused the saturation magnetic flux density to decrease.

[0037] [Additional manufacturing test] As mentioned above, the single roll method may be used in the process of manufacturing alloy ribbons. In the single roll method, the molten metal is rapidly cooled and solidified with a copper cooling roll to obtain a thin body, so the alloy ribbon may contain Cu. Therefore, as an additional test, the results of an investigation into the case where the alloy contains Cu are shown in Figure 3. In the additional test, alloy ribbons were obtained in the same manner as in the above manufacturing test, and were evaluated in the same manner.

[0038] As shown in FIG. 3, in Example 10, in which Cu was not contained in the alloy, the saturation magnetic flux density Bs, the coercive force Hc, and the crystallization rate were all evaluated as good. In Example 11, Cu was contained at 0.3 atomic %, but the saturation magnetic flux density Bs, the coercive force Hc, and the crystallization rate were equivalent to those of Example 10, and the evaluation was obtained as good. In contrast, in Comparative Example 6, Cu was contained at 0.7 atomic %, but the saturation magnetic flux density Bs was a small value of 1.59 [T]. This was thought to be due to the excessive Cu content, which resulted in a decrease in the Fe content and a decrease in the saturation magnetic flux density. In other words, it was found that although Cu cannot be contained in excess, a content of 0.3 atomic % or less does not affect the above-mentioned judgment.

[0039] The composition range of the Fe-based alloy that can provide soft magnetic properties substantially equivalent to those of the Fe-based amorphous alloys including those in the above-mentioned embodiments is determined as follows.

[0040] Si, B, and C are amorphous forming elements, and they cooperate with each other to form an amorphous phase in the alloy ribbon. On the other hand, excessive Si content reduces the amorphous forming ability and reduces the saturation magnetic flux density of the resulting Fe-based amorphous alloy. Excessive B content causes compound phases such as Fe3B and Fe2B, which have high crystalline magnetic anisotropy, to precipitate, and also increases costs. Excessive C content reduces the crystallization temperature from the amorphous phase, inducing crystallization of crystal grains. Taking these factors into consideration and the balance of the content of each element, the content was determined as follows. That is, Si is within the range of 1 to 5%, preferably within the range of 1 to 2%, in atomic %. Also, B is within the range of 5.5 to 13%, preferably within the range of 10 to 13%, in atomic %. Also, C is within the range of 1 to 7%, preferably within the range of 1 to 2%, in atomic %. However, in order to ensure the content of Fe, Si+B+C<15.0 atomic %.

[0041] P is an amorphous forming element, and although it does not have much interaction with other amorphous forming elements, increasing its content alone can increase the amorphous forming ability. On the other hand, excessive P content reduces the saturation magnetic flux density of the resulting Fe-based amorphous alloy. Taking these factors into consideration, the P content is within the range of 0.1 to 4 atomic percent.

[0042] Cu is a non-magnetic material, and if it is contained in a small amount, it does not affect the soft magnetic properties of the resulting Fe-based amorphous alloy. On the other hand, if it is contained in an excessive amount, it results in a decrease in the Fe content, which leads to a decrease in the saturation magnetic flux density. Taking these into consideration, Cu can be contained in an atomic percent of 0.3% or less.

[0043] Fe is a main component element and is contained as the balance to the above elements, and can increase the saturation magnetic flux density. On the other hand, if it is contained in excess, it becomes difficult to obtain an amorphous single phase. Taking these into consideration, Fe is in the range of 82 to 85 atomic %.

[0044] Although the representative embodiments of the present invention have been described above, the present invention is not necessarily limited thereto, and a person skilled in the art will be able to find various alternative embodiments and modifications without departing from the spirit of the present invention or the scope of the appended claims. For example, the Fe-based amorphous alloy according to the present invention may be a pulverized powder material.

Claims

1. In atomic percent, Si: 1 to 5%, B: 5.5-13%, C: 4.0 to 7%, P: 3.0-4% However, Si+B+C<15.0%, An Fe-based amorphous alloy, characterized in that, among an amorphous single-phase alloy having a composition consisting of Fe and unavoidable impurities with the remainder being the composition, Fe is 82-85%, the saturation magnetic flux density Bs is greater than 1.60 [T], and the coercive force Hc is less than 10 [A / m].

2. 2. The Fe-based amorphous alloy according to claim 1, further comprising, in atomic percent, 0.3% or less of Cu.

3. 3. The Fe-based amorphous alloy according to claim 1, characterized in that it has an amorphization rate of more than 98%.

4. In atomic percent, Si: 1 to 5%, B: 5.5-13%, C: 4.0 to 7%, P: 3.0-4% However, Si+B+C<15.0%, A master alloy having a composition with the balance being Fe and unavoidable impurities is melted, A method for producing an Fe-based amorphous alloy, comprising: rapidly solidifying the master alloy so that the master alloy is amorphous in a single phase, contains 82 to 85% Fe, has a saturation magnetic flux density Bs of more than 1.60 [T], and has a coercive force Hc of less than 10 [A / m].

5. 5. The method for producing an Fe-based amorphous alloy according to claim 4, wherein the mother alloy contains, in atomic percent, 0.3% or less of Cu.

6. 6. The method for producing an Fe-based amorphous alloy according to claim 4, wherein the alloy is rapidly solidified so as to give an amorphous ratio of 98% or more.

Citation Information

Patent Citations

  • Fe-based amorphous alloy with high saturation magnetic induction intensity and strong amorphous forming ability

    CN105088107A

  • Iron-based amorphous alloy and preparation method thereof

    CN106636982A

  • Fe based amorphous alloy thin strip having high magnetic flux density

    JP2002285304A

  • Thin ribbon of amorphous iron alloy

    JP2006316348A

  • Fe-BASED AMORPHOUS ALLOY THIN STRIP

    JP2009007639A